Rain water harvesting and recycling technology for sustainable use of small agricultural watersheds* - ADAV, R P Y; AGGARWAL, R K; SINGH, PRATAP; ARYA, S L; PRASAD, RAM; TIWARI, A K; BHATTACHARY, P; YADAV, M K (The Indian Journal of Agricultural Sciences, 2011)
The technology of rainwater harvesting and recycling developed and tested at village Johranpur in Solan district of Himachal Pradesh has proved very effective. Run off in the range of 16.4 to 29.5 % of rainfall received during monsoon was harvested and recycled back to the contributing area. It resulted in 1.7 and 3.2 times wheat yield wit11 1 and 2 supplemental irrigations respectively. Alternative crops like tomato, ginger and brinjal provided higher gross return / unit use of harvested rainwater. Better returns from alternative crops favoured diversification in the watershed and area under traditional maize-wheat rotation decreased from 91 to 49 %. This modelitechnology can be replicated in the regions receiving annual rainfall > 1000 mm and having gentle to moderate slope to produce run off of more than 25 cm for sustainable agriculture production from small watershed.